PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Siti Aminah (UNISAN JURNAL, 2024)
This research aims to examines the efforts of Islamic Religious Education teachers in fostering the morals of the students of SMK IP Fathul Ulum . The formulation of the problem in this thesis is the efforts of Islamic Religious Education teachers in fostering the morals of the students of SMK IP Fathul Ulum . The type of this research is field research using a qualitative descriptive approach. In data collection used data collection techniques in the form of purposive sampling, snowball sampling. The method used in data collection is the observation method as the main method, the interview method and the documentation method as a supporting method. While the data analysis used qualitative analysis with the stages of data reduction, data presentation, and drawing conclusions. Conclusions are drawn by means of inductive thinking. The results showed that the efforts of Islamic Religious Education teachers in fostering the morals of SMK IP Fathul Ulum students were through habituation, example, punishment, advice, learning, controlling, coaching, giving assignments, lectures, questions and answers, stories, targhib (motivating love of kindness). ), tarhim (prohibition), bil wisdom (wise) and deliberation. However, Islamic religious education teachers have not evaluated, that is, they have not held brainstorming, identified problems, analyzed problems with certain techniques, looked for alternative solutions, determined problem solving actions, planned actions, took actions and evaluated actions.